2021
DOI: 10.1136/archdischild-2020-319926
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hyperglycaemia is associated with worse neurodevelopmental outcomes in extremely preterm infants

Abstract: ObjectiveTo assess the associations between neonatal hyperglycaemia and insulin treatment, versus long-term neurodevelopmental outcomes in children born extremely preterm.Design and settingObservational national cohort study (Extremely Preterm Infants in Sweden Study) using prospectively and retrospectively collected data. Neurodevelopmental assessment was performed at 6.5 years of age.Patients533 infants born <27 gestational weeks during 2004–2007; 436 survivors were assessed at 6.5 years.Outcome measuresN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 29 publications
0
35
0
2
Order By: Relevance
“…23 Hyperglycaemia and hypertriglyceridaemia are associated with increased mortality and morbidity in very preterm infants. [24][25][26] In both arms of the same trial, 50% developed blood urea levels >7 mmol/L, with 50% developing blood urea >10 mmol/L in the high intake arm, suggesting intakes exceeding anabolic capacity with the current recommended intakes. Indeed, studies of higher intakes of macronutrients in very preterm babies in the early postnatal period are associated with other metabolic derangements, including the refeeding syndrome.…”
Section: Original Researchmentioning
confidence: 98%
“…23 Hyperglycaemia and hypertriglyceridaemia are associated with increased mortality and morbidity in very preterm infants. [24][25][26] In both arms of the same trial, 50% developed blood urea levels >7 mmol/L, with 50% developing blood urea >10 mmol/L in the high intake arm, suggesting intakes exceeding anabolic capacity with the current recommended intakes. Indeed, studies of higher intakes of macronutrients in very preterm babies in the early postnatal period are associated with other metabolic derangements, including the refeeding syndrome.…”
Section: Original Researchmentioning
confidence: 98%
“…One further study was excluded following full-text review due to the lack of a full text [ 24 ] and two others were excluded due to the lack of control groups [ 20 , 25 ]. Thus, a total of 6 studies were included, comprising 2226 infants at enrolment, with neurodevelopment assessment available in 1059 (48%) infants [ 19 , 26 , 27 , 28 , 29 , 30 ]. Meta-analysis was not performed due to the heterogeneity of the studies, especially the tools used to assess long-term neurodevelopment outcome.…”
Section: Resultsmentioning
confidence: 99%
“…We found that early fluctuations in glucose levels were also independently associated with both a lower GA and suboptimal neurological outcomes, in line with a previous study that reported an association of neonatal hyperglycemia with impaired neurodevelopmental outcomes in extremely preterm infants. 24 This highlights the necessity to correct plasma sodium levels for glucose levels when attempting to determine whether acute changes in plasma sodium may lead to adverse neonatal outcomes.…”
Section: Discussionmentioning
confidence: 99%